2020
DOI: 10.1002/prp2.690
|View full text |Cite
|
Sign up to set email alerts
|

Safety and nonclinical and clinical pharmacokinetics of PC945, a novel inhaled triazole antifungal agent

Abstract: PC945 is a novel antifungal triazole formulated for nebulized delivery to treat lung Aspergillus infections. Pharmacokinetic and safety profiles from nonclinical studies and clinical trials in healthy subjects, and subjects with mild asthma were characterized. Toxicokinetics were assessed following daily 2‐hour inhalation for 14 days. Potential for drug‐drug interactions was evaluated using pooled human liver microsomes. Clinical safety and pharmacokinetics were assessed following (a) si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Opelconazole is a novel antifungal triazole that was designed and optimized for inhalation via commonly available nebulizers [ 179 ]. After inhalation, opelconazole shows efficacy primarily in the lungs (systemic concentrations are minimal), making it a promising agent for treating pulmonary aspergillosis in non-neutropenic patients without disseminated infection.…”
Section: Antifungal Drugs In Clinical Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Opelconazole is a novel antifungal triazole that was designed and optimized for inhalation via commonly available nebulizers [ 179 ]. After inhalation, opelconazole shows efficacy primarily in the lungs (systemic concentrations are minimal), making it a promising agent for treating pulmonary aspergillosis in non-neutropenic patients without disseminated infection.…”
Section: Antifungal Drugs In Clinical Developmentmentioning
confidence: 99%
“…Recent in vitro and in vivo studies have shown distinctive pharmacological characteristics, differentiating from commonly used azoles. Chemical and physical attributes of opelconazole, namely increases in lipophilic compounds and micronized drug particles, result in high local concentrations, prolonged lung retention, slow absorption form the lung, and as a consequence, low plasma concentrations [ 179 ].…”
Section: Antifungal Drugs In Clinical Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In a phase I trial, PC945 was well tolerated in healthy controls and subjects with mild asthma [64].…”
Section: Pc945mentioning
confidence: 99%
“…PC945 is a potent inhibitor of ergosterol synthesis, exhibiting 14-fold greater potency than voriconazole and 2.6-fold more potency than posaconazole against A. fumigatus [ 96 ]. A Phase 1 study in healthy volunteers and adult asthmatic patients (NCT02715570) showed that following inhalation, PC945 was slowly absorbed from the lung and led to low systemic exposure, suggesting an improved safety and DDI profile relative to oral itraconazole [ 97 ].…”
Section: Pur1900: Inhaled Itraconazolementioning
confidence: 99%